Body temperature triggered shape‐memory polymers with high elastic energy storage capacity. Issue 14 (13th January 2016) - Meng, Yuan; Jiang, Jisu; Anthamatten, Mitchell
ABSTRACT: Shape‐memory polymers (SMPs) that respond near body temperature are attracting broad interest, especially in the biomedical fields. In this study, the triggering temperature of poly(caprolactone) SMP networks is precisely adjusted by inclusion of non‐crystallizable molecular linkers and by variation of prepolymer molecular weight. Longer, non‐crystalline linkers and lower molecular weight prepolymers interfere with crystallization, lowering the transition temperature. Networks are prepared with crystallization temperatures that are beneath the human body temperature and yet are above room temperature. Upon cooling such amorphous networks to room temperature, crystallization is sluggish. There, elastomers can be easily strained by several hundred‐percent to induce crystallization, thereby fixing strained states. If subsequently heated, programmed SMPs can release significant amounts of stored strain energy (∼3 MJ/m 3 ). SMPs that combine elastic energy storage and exhibit triggering temperatures near the human body temperature could benefit emerging applications in the biomedical space. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1397–1404 Abstract : Shape‐memory polymers (SMPs) that respond near body temperature are attracting broad interest, especially in the biomedical fields. A semi‐crystalline SMP's melting transition temperature is tuned by incorporating non‐crystalline molecular linker groups and by altering the network prepolymer molecular weight. Optimized networks exhibit melting temperatures between room temperature and the human body temperature, and, upon triggering, the networks are capable of releasing large amounts of elastic energy. This straightforward technology could benefit numerous biomedical applications. Photo by J. Adam Fenster, University of Rochester.